Knowledge, attitude, and practice on diabetic retinopathy among final-year medical students in Riyadh - Amro Alhazimi (Wolters Kluwer Medknow Publications, 2024)
Introduction: This study aimed to evaluate the awareness, knowledge, and attitude on diabetic retinopathy of final-year medical students and the association of knowledge, attitude, and practice with the gender of medical students. Methods: A descriptive cross-sectional study was conducted at the College of Medicine, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi Arabia. The initial part of the questionnaire included demographic details, while the remaining parts of the questionnaire included six questions on knowledge, four on attitude, and three on practice. IBM SPSS Statistics 24 was used to retrieve and analyze data from an Excel file. A P value <0.05 was considered as statistically significant. Results: Of 84 medical students, 51 (60.71%) and 33 (39.19%) were male and female medical students, respectively. The total knowledge score for male and female medical students was 4.28 (SD = 0.92). The majority of students correctly answered practice questions, indicating good significant practice toward diabetic retinopathy among diabetic patients with A score of 1.93 (SD = 0.83). Conclusion: The majority of final-year medical students were good in knowledge and practice toward prevention and treatment of diabetic retinopathy, which helps them become better future care providers for patients with diabetes and diabetic retinopathy.